Hepatocyte Growth Factor Levels in the Saliva and Gingival Crevicular Fluid in Smokers with Periodontitis - Sukumaran Anil (Disease Markers, 2014)
Hepatocyte growth factor (HGF) production by oral fibroblasts is enhanced by various molecules that are induced during inflammatory conditions including periodontitis. HGF plays an important role in the progression of periodontitis, by stimulating intense growth of epithelial cells and preventing regeneration of connective tissue attachments. Smokers have a greater risk factor in the pathogenesis and progression of periodontal disease. The objective of the study was to estimate the level of HGF in saliva and gingival crevicular fluid (GCF) in smokers with periodontitis and to compare these levels with that of nonsmokers with periodontitis and healthy controls. The HGF levels were found to be significantly high in the saliva and GCF of smokers with periodontitis compared to both never-smokers with periodontitis and the healthy control group. The elevated levels of HGF in the saliva and GCF in the study population could explain the intrinsic mechanism triggering the severity of the periodontitis in smokers. Further studies are necessary to validate the current observations and to establish a sensitive marker to predict periodontal disease activity.